Área e volume: a transição da noção de medida à de área e de volume - Godoy, Elaine Alves de [UNESP] (2014)
The main object of this work is study some elementary comcepts in Euclidean geometry. After studying the scissors-congruence between polygons, we prove the Bolayi-Gerwein theorem. We study also this concept for polyhedra and we see the Dehn theorem which claims that in the case of polyhedra the equality between the volume and the scissors-congruence are not equivalent in general. Finally, we present some activities where it is possible to check by an intuitive and a deductive manner the congruence by cutting between some polygons with the same area